43.4k views
5 votes
Solve equation using zero product property -9n(5n-5)=0

User Estani
by
6.0k points

1 Answer

4 votes
Divide -9n from both sides. 0 divided into anything will still be 0.


5n - 5 = 0

Add 5 to both sides.


5n = 5

Divide both sides by 5 to get n by itself.


n = 1

Plug this value into the initial equation.


-9(1) * (5(1) - 5) = 0


-9 * (5 - 5) = 0


-9 * 0 = 0


0 = 0

This proves that n = 1.

Zero product property is applied when the factor (5n - 5) is set to be equal to 0.
User Gabe Thorns
by
5.7k points